Dietary supplements for sports enthusiasts - effective support or the impact of marketing campaigns? A narrative review - Hauzer, Paula; Kaniak, Aleksandra; Zielska, Julianna; Protsenko, Yuliia; Forszt, Kacper; Andrzejewska, Julia (Quality in Sport, 2026)
Introduction and objective: Dietary supplements are becoming increasingly popular, especially among physically active people, regardless of their level of experience. In Poland, as many as 90% of adults use such products, which highlights their importance in everyday life. The reasons for using supplements are varied, ranging from actual health needs to the influence of intensive marketing. Given the huge number of products available and insufficient market supervision, it is crucial to understand the principles of their use. The aim of this study is to assess the validity of supplementation among physically active people in the context of real health needs and the impact of marketing on consumer decisions. Abbreviated description of the state of knowledge: Supplements are products that supplement the diet and contain concentrated ingredients with physiological effects. Unlike drugs, they do not undergo rigorous clinical trials. They are often used without consulting experts, and knowledge about them comes mainly from advertising and the media. The Australian Institute of Sport (AIS) has divided supplements into four groups, A-D, according to their effectiveness and safety. Professional athletes usually seek the help of specialists, while amateurs often choose supplements on their own, which carries a risk of error. Products that support recovery, performance, and concentration are particularly popular. Social media, through influential celebrities, often promote unverified information. Summary: Supplements can support the health of physically active people, but their use should be informed and consulted with specialists. Excessive trust in advertising and a lack of knowledge increase the risk of misuse of these products. Education, legal regulations, and professional advice are key to safe supplementation.